Ovos produzidos em diferentes sistemas de alojamento: qualidade e segurança microbiológica, parâmetros físicos, validação e utilização de método multiresíduo para detecção de antimicrobianos e pesticidas - Galvão, Júlia Arantes [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The livestock production has been modified gradually due to several socio-cultural changes worldwide. Increasing the demand for food produced considering animal welfare. In this context also is laying hen raising. New systems are being proposed to improve the living conditions of laying hens, foremost among them the free range (FR). There are few studies which evaluated the quality and safety of eggs produced in these new environments. Thus was proposed in this study the evaluation of eggs and production environment from three laying hens farms (two under the conventional system of creation and one system in FR), two of them (FR and Conventional 1) located on the same property, which decreased the chances of introducing macroclimate and breeder lines bias. Salmonella was surveyed in the production environment, drinking water and food, and the shells of the eggs, which were also enumerated enterobacteria. It was also evaluated the physical quality of the eggs and proceeded to the validation of a multiresidue method for analysis of pesticides and antibiotics, used for quantifying the content of the eggs of the three farms. In FR the largest system Enterobacteriaceae counts (p <0.001) was detected and Salmonella were found in three eggshells and at one feeder (S. Senftenberg), the pathogen was not detected in other environmental samples, or food and water. The eggs of the FR system had lower weight, greater shell thickness and concentration of albumen. The multiresidue method is effective in the recovery of all compounds, enabling the validation of the proposed technique. Enrofloxacin residues were detected in five out of thirty samples from the RF system, they all have extrapolated the MRL of 10μgL-1 established by the Ministry of Agriculture, Livestock and Supply. The FR system showed greater vulnerability and sanitary conditions regarding the presence of antimicrobial residues. As regards physical characteristics, they do not confer to ...

A criação de animais de produção vem se modificando gradualmente devido a diversas alterações socioculturais em todo o mundo. Cada vez mais se tem observado a demanda por alimentos produzidos considerando-se o bem estar animal. Neste contexto também encontra-se a avicultura de postura. Novos sistemas vêm sendo propostos para melhorar as condições de vida das galinhas poedeiras, destacando-se entre eles o free range (FR). São poucos os trabalhos que avaliaram a qualidade e segurança dos ovos produzidos nesses novos ambientes. Assim foi proposta neste estudo a avaliação de ovos e ambiente de produção de três granjas de postura comercial (duas no sistema convencional de criação e uma no sistema FR), sendo duas delas (FR e Convencional 1) localizadas em uma mesma propriedade, o que diminuiu a chance de introdução de viés de macroclima e linhagem. Foi pesquisada Salmonella no ambiente de produção, água de bebida e ração, além das cascas dos ovos, onde também foram enumeradas enterobactérias. Avaliou-se também a qualidade física dos ovos e procedeu-se à validação de um método para análise de multiresíduos de antimicrobianos e defensivos agrícolas, utilizado para sua quantificação no conteúdo dos ovos das três granjas. No sistema FR foi foram verificadas as maiores contagens de enterobactérias (p < 0,001) e detectada Salmonella em três cascas de ovos e em um comedouro (S. Senftenberg), o patógeno não foi detectado nas outras amostras ambientais, ou de ração e água. Os ovos do sistema FR apresentaram menor peso total, maior espessura de casca e concentração de albúmen. O método multiresíduo se mostrou eficaz na recuperação de todos os compostos, possibilitando a validação da técnica proposta. Foram detectados resíduos de Enrofloxacina em cinco de trinta amostras provenientes do sistema FR, todos eles extrapolaram o LMR de 10μgL-1 estabelecido pelo Ministério da Agricultura Pecuária e ...
Keywords: Ovos - Produção; Salmonella; Microbiologia; Segurança alimentar; Food security